1964
DOI: 10.1111/j.1745-3984.1964.tb00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of College Grades for All Public Colleges of a State

Abstract: Not infrequently studies are published concerning the prediction of grades in a single college for a single year's entering students.However, it is rare to find studied together a large number of colleges over several years' time. Without mere general study than that of the single c~llege for a single year, one can say little about what to expect in a new situation in terms of level of prediction, fluctuations from year to year, the gain to be obtained from using as predictors test scores in addition to record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

1966
1966
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
2
9
1
Order By: Relevance
“…These results compare to the findings reported by Hills (1964). Hills' University of Georgia study reported similar multiple correlations between high school GPA, admission test score, and fi-eshman GPA.…”
Section: Hypothesiscontrasting
confidence: 55%
See 4 more Smart Citations
“…These results compare to the findings reported by Hills (1964). Hills' University of Georgia study reported similar multiple correlations between high school GPA, admission test score, and fi-eshman GPA.…”
Section: Hypothesiscontrasting
confidence: 55%
“…Research on the prediction of college GPA significantly expanded in the post-World War II era with an emphasis on conventional predictor variables such as high school GPA (Hills, 1964), high school graduation class rank (McDonald & McPherson, 1975), and aptitude test scores (Noble & Sawyer, 1989;Nisbet, Ruble, & Schurr, 1982).…”
Section: The Prediction Of College Gpamentioning
confidence: 99%
See 3 more Smart Citations